Effect of Seaweed Liquid Fertilizer on the Growth, Biochemical Constituents and Yield of Tagetes erecta, under Field Trial - R. Rengasamy2, S. Sridhar1* and (Journal of Phytology, 2010)
<span style="line-height: 110%; font-family: ";Book Antiqua";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The efficacy of Seaweed Liquid Fertilizer of different concentrations obtained from green seaweed Ulva lactuca was assessed on the growth, pigments, total chlorophyll, total protein, total carbohydrate and total lipid and the yield of a flowering plant Tagetes erecta. The combined effect of 1.0% SLF of<span style="line-height: 110%; font-family: ";Times New Roman";,";serif";; color: #494949; font-size: 10.5pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> <span style="line-height: 110%; font-family: ";Book Antiqua";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">U. lactuca<span style="line-height: 110%; font-family: ";Book Antiqua";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> with different proportions of recommended rate of chemical fertilizers was also made on the test plant. Among the concentrations, plants that received with 1.0% SLF and 50% recommended rate of chemical fertilizers showed a maximum growth characteristic, number and fresh weight of flowers.